Cardiovascular risk factors and social determinants in a population study in Rio de Janeiro, Brazil. (30th September 2020) - Ferreira, L; Flumignan, V; Marinho, B; Sampaio, F; Morais, J; Botelho, B; Mello, T; Silva, R; Fernandes, A; Muxfeldt, E
Abstract: Background: The association of cardiovascular (CV) diseases and their risk factors with socioeconomic status has been well described, but its influence is often underestimated in epidemiological studies in Brazil. Objective: To evaluate the relationship between the main CV risk factors and socioeconomic indicators in a population of adults registered in a Family Health Care (FHC) unit in a great urban center - Rio de Janeiro, Brazil. Methods: Cross-sectional population study that included adults aged between 20 and 50 years living in the area covered by the FHC unit in Rio de Janeiro. Demographic data (gender and age), socioeconomic data (education level, profession, employment), CV risk factors (smoking, sedentary lifestyle, obesity, hypertension, diabetes, dyslipidemia) were recorded. The metabolic profile is evaluated through laboratory tests. Those who studied up to high school were considered poorly educated. Results: 604 individuals were enrolled [39% male, mean age: 38.8 ± 8, 9 years] The median of schooling was 12 years. 288 individuals had high schooling, 44.5% were male. A total of 130 individuals did not study or work. Women with low education had a higher risk of smoking, obesity and hypertension with no difference regarding labor or study activities. Otherwise, men with low education had a higher risk of sedentary lifestyle and hypertension. Among men, not working or studying increased the risk of smoking and hypertension. Conclusions: We found an inverse association between socioeconomic conditions and the prevalence of CV risk factors. Women are more affected by low schooling, while men are more affected by their working occupation. The study suggests that socioeconomic factors influence the CV risk, affecting men and women differently, pointing to the need for more comprehensive public health policies that effectively reverse this situation. Key messages: We found an inverse association between socioeconomic conditions and the prevalence of CV risk factors. Socioeconomic factors influence cardiovascular risk differently according to gender.